2012
DOI: 10.5367/te.2012.0133
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Visitors' Expenditures in a Tourist Destination: OLS, Quantile Regression and Instrumental Variable Estimators

Abstract: The impact of tourism on the local economy and employment has been widely reported in the literature through the use of regional or county expenditure multipliers. Indeed, the money that visitors spend in a community is likely to be the benefit that residents probably recognize most readily. Despite this, only a few studies have focused on the determinants of tourist expenditure at the individual or household level. This paper sheds further light on this issue. For this purpose, the authors use information gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
(53 reference statements)
0
28
0
Order By: Relevance
“…Following the example of Santos and Cabral Vieira (2012), an OLS regression was first used to estimate the coefficients based on the conditional mean. The quantile regression approach was then applied to take into consideration unobserved heterogeneity across quantiles and heteroscedasticity among the error terms.…”
Section: Methodsmentioning
confidence: 99%
“…Following the example of Santos and Cabral Vieira (2012), an OLS regression was first used to estimate the coefficients based on the conditional mean. The quantile regression approach was then applied to take into consideration unobserved heterogeneity across quantiles and heteroscedasticity among the error terms.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, it is worth reemphasizing that the goal of IV regression is to obtain a correct estimate of an endogenous explanatory variable and not to maximize the R-squared. Santos and Vieira (2012) recently used IV regression when examining how a number of determinants explained variation in micro-level tourism expenditures. Based on knowledge gained from the human capital literature, they considered (the amount of) education as a possible endogenous variable and found that the IV estimates for tertiary schooling tended to be higher than the analogue OLS estimates.…”
Section: Comparing Ols and IV Estimatesmentioning
confidence: 99%
“…In this regard, the education level of tourists has not really been considered an important predictor of tourism expenditure at the micro level (Marcussen, 2011). Therefore, the remedy proposed by Santos and Vieira (2012) likely has small practical consequences. Nor did these authors provide any information about the instruments they used, which is the topic of the next subsection.…”
Section: Comparing Ols and IV Estimatesmentioning
confidence: 99%
“…The literature suggests that the most common technique for estimating tourist expenditure is ordinary least squares (OLS) regression (Thrane 2014). Apart from OLS, the quantile regression model has been found to present a more comprehensive picture by incorporating heterogeneity from expenditure distribution (e.g., Lew and Ng 2012; Santos and Cabral Vieira 2012; Hung, Shang, and Wang 2012) in order to fully understand tourist expenditure and provide more accurate information to tourism marketers. The explanatory variables of tourist expenditure can be categorized as economic, social, psychological, trip-related, and destination-related (Yi.…”
Section: A Review Of Relevant Literature and Theorymentioning
confidence: 99%